Collective Bargaining and The Performance Rating in Italy - Grandi, Barbara (Advances in Social Sciences Research Journal, 2014)
The big changes that have framed economies and societies all over Europe in the past decades have led to a changing role of the collective bargaining in the objectives it is pursuing[1]. This summary, presenting an overview on collective bargaining in Italy, is going to focus over the possibility for a collective agreement to determine the practices for better performance, the evaluation of such performances, as well as the connected monetary and/or non monetary recognition, in other words, the possibility for workers and their representatives to rate their own performance.